Niche partitioning among demersal marine fishes at the southern tip of South America - Alvarez, C. D. (2024)
Niche differentiation is a means by which species can coexist and avoid competition. In marine food webs, large demersal fish often couple different trophic pathways and can be targets of valuable fisheries. This is the case for long tail hake Macruronus magellanicus, Patagonian toothfish Dissostichus eleginoides, southern blue whiting Micromesistius australis, and southern hake Merluccius australis, which coexist in the southernmost region of the southwestern Atlantic Ocean. In this study, C and N stable isotope and stomach content analyses were used to evaluate possible niche partitioning among these 4 species. Long tail hake and southern blue whiting mainly eat crustaceans, with great overlap in their diet spectra, but they differentiate in their spatial distribution. Southern hake and Patagonian toothfish mainly feed on fish, including the other 2 species, and exploit prey from a broad spatial area. These results suggest a spatial compartmentation of the food web at lower trophic levels, with demersal fish at the higher levels linking distant compartments. Therefore, results of this study show similarities and differences among these 4 demersal fish species, in the trophic and spatial dimensions of their niches, suggesting niche differentiation and probably different roles in the food web.